Dearest daughter - Ferguson, Alison, 1954- ([Eleebana, NSW] : Backstory Press, 2021)
Dearest Daughter is the second of three in The Sisters' Saga, which tells of three sisters and the compromises they must make to reconcile love's delusions with the demands of reality. In this short historical fiction novel, the lives of the younger sisters, Rose and Beth Burbridge are turned upside down by Henrietta's return from India. In colonial Sydney between 1825-35, Henrietta asks why, if matrimony is the bedrock of the family, is it so hard for love to survive marriage? But her sisters must answer a very different question: How much would they trade for matrimony?
Prepublication record (machine generated from publisher information)
Keywords: Sisters -- Fiction; Families -- Fiction; Historical fiction; Historical fiction; Sydney (N.S.W.) -- 19th century -- Fiction; Australian